Effect of Rumen Modifier on Methanogenesis and Feed Digestibility under in Vitro Conditions - Lakhani, Neeti; Kamra, Devki Nandan; Lakhani, Preeti; Kala, Anju (Indian Journal of Animal Nutrition, 2019)
A rumen modifier which is a mixture of RM-7 [neem seed cake (Azadirachta indica), mahua seed cake (Madhuca longifolia), fennel seed (Foeniculum vulgare), harad (Terminalia chebula), fruit pulp of bahera (Terminalia bellirica), fruit pulp of amla (Phyllanthus emblica) and ajwain seed (Trachyspermum ammi) mixed in 2:2:2:1:1:1:1 proportion] was tested at 0 (control), 5, 10, 15 and 20% of the substrate along with 0.06% of sodium sulphate (except control) for their effects on in vitro methane production and feed fermentation. Inclusion of RM-7 at 5, 10, 15 and 20% of substrate along with 0.06% of sodium sulphate did not affect gas production but there was significant (p